Wear behaviour of nickel coatings reinforced by recycled quarry dust: Influence of current density - Othman, Intan Sharhida; Munawar, Rose Farahiyan; Liew, Pay Jun; Mohd Abid, Mohd Asyadi Azam; Abd Razak, Jeefferie; Sundi @ Suandi, Syahrul Azwan; Kamis, Shahira Liza; Alhamoudi, Fahad Hussain (Penerbit Akademia Baru, 2025)
Nickel coatings incorporated with quarry dust were synthesized through direct current electrodeposition from a nickel Watt’s bath. The study explored the effects of varying current densities on the surface morphology and wear behaviour of the nickel-quarrydust (Ni-QD) composite coatings deposited on a high-speed steel (HSS) substrate. Quarry dust was chosen as a reinforcement material due to its high silica and alumina content, which enhance the properties of the coating. To achieve finer particle size, the quarry dust was subjected to ball milling before electrodeposition. The study tested a range of current densities from 2 to 8 A/dm², as different current densities produce different results. The composite coatings were characterized using a Scanning Electron Microscope (SEM) and their wear resistance was evaluated through pin-on-disk test. The results indicated that increasing the current density enhanced the wear resistance of the coatings. Coatings produced at high current densities displayed a colony-like structure, demonstrating the impact of deposition conditions on colony size relative to current density. Ni-QD composite coatings created at 6 and 8 A/dm² resulted in smoother and narrower wear scars with minimal scratching, attributed to the low surface roughness of the coatings.